How many medieval and early modern manuscripts were copied by female scribes? A bibliometric analysis based on colophons - Åslaug Ommundsen; Aidan Keally Conti; Øystein Ariansen Haaland; Bodil Holst (Humanities & Social Sciences Communications)
Abstract A monk at his desk, copying a manuscript, is a typical image associated with the Middle Ages, but what about the women? According to a recent estimate more than 10 million hand-written manuscripts were produced in the Latin West (the Roman Catholic part of Europe) between 400 and 1500 CE with around 750000 still preserved. Despite this abundance no attempt has been made up till now to quantify women’s contribution to manuscript production. Here we address the research question: What was the quantitative contribution of female scribes based on available sources? The objective of this paper is to present the first bibliometric analysis of the contribution of female scribes. The analysis is based on colophons. Colophons are short statements sometimes added to a manuscript supplying information such as name(s) of the scribe(s), name(s) of the person(s) who commissioned the manuscript, place and date of production and in some cases personal reflections from the scribe. We use the Benedictine colophon catalogue with 23774 entries and find that 1.1% (dating from around 800 to 1626 CE) can be identified with certainty as having been copied by female scribes (95% confidence interval: 0.9% to 1.2%). This is to be considered a lower-bound estimate. Using existing estimates for manuscript production and loss we may infer, under the assumption that the estimates are valid, that at least 110000 manuscripts were copied by female scribes, of which around 8000 should still exist. Our investigation provides evidence for a small, but steady contribution from female scribes throughout the Middle Ages. While the number of verifiable female scribes is low, at the same time our study suggests that there must be several female scribes and book-producing communities that have not yet been identified.